Meningkatkan Kemampuan Siswa SMP N 18 Surakarta dalam Mengembangkan Media Poster Melalui Platform Canva - Wicaksono, Dipo; Nadya Puspita Adriana (Yayasan Literasi Sains Indonesia, 2023)
In today's era, most of the use of electronic goods such as computers, mobile phones and gadgets in teenagers is only used for social media, browsing and playing games, without being able to produce works of art. Knowledge of other functions of the use of these goods has not been well polarized so that it has a bad influence. Lots of applications that can be used Conducive and fun learning in the industrial revolution 4.0 makes changes in learning styles in the learning process, one of which is Canva. Canva is a service for creating learning content such as infographics, posters, banners, presentations that are very helpful in the process of learning activities. So that it can be used to create online learning media. One of the learning media that wastrained was to make posters with the theme of adiwiyata. Adiwiyata is one of the programs of the Ministry of Environment in order to encourage the creation of knowledge and awareness of school residents in an effort to preserve the environment, one of which is at SMPN 18 Surakarta. In this program, it turns out that many students do not know the Canva application, so students are enthusiastic to take part in this training by developing their talents and imagination. The results of the training turned out to have a positive impact on students and the school itself with the abilities of their students, and for the school to really appreciate the training to improve the soft skills of its students